Clinical predictive value of naïve and memory T cells in advanced NSCLC - Zhang, Guan; Liu, Aqing; Yang, Yanjie; Xia, Ying; Li, Wentao; Liu, Yunhe; Zhang, Jing; Cui, Qian; Wang, Dong; Liu, Xu; Guo, Yongtie; Chen, Huayu; et al. (Frontiers in Immunology, 2022)
Currently, there is no sensitive prognostic biomarker to screen out benefit patients from the non-benefit population in advanced non-small cell lung cancer patients (aNSCLCs). The 435 aNSCLCs and 278 normal controls (NCs) were recruited. The percentages and absolute counts (AC) of circulating naïve and memory T lymphocytes of CD4+ and CD8+ T cells (Tn/Tm) were measured by flow cytometry. The percentage of CD4+ naïve T (Tn), CD8+ Tn, CD8+ T memory stem cell (Tscm), and CD8+ terminal effector T cell decreased obviously. Still, all AC of Tn/Tm of aNSCLCs was significantly lower compared to NCs. Higher AC and percentage of CD4+ Tn, CD8+ Tn, and CD4+ Tscm showed markedly longer median PFS in aNSCLCs. Statistics demonstrated the AC of CD4+ Tn (≥ 3.7 cells/μL) was an independent protective factor for PFS. The analysis of the prognosis of immunotherapy showed the higher AC and percentage of CD4+ Tn and CD4+ Tscm and higher AC of CD8+ Tscm had significantly longer median PFS and the AC of CD4+ Tn (≥ 5.5 cells/μL) was an independent protective factor for PFS, moreover, higher AC and percentages of Tn/Tm suggested higher disease control rate and lower progressive disease rate. The AC of Tn/Tm showed more regular patterns of impairment and was more relative with the disease progression than percentages in aNSCLCs. AC had a better predictive value than percentages in Tn/Tm for PFS. Notably, the AC of CD4+ Tn was a potential prognostic biomarker for the PFS and efficacy of immunotherapy.